2022
DOI: 10.1101/2022.03.31.486614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Competition for H2A.Z between genes and repetitive elements establishes response to anti-viral immune activation

Abstract: Activation of endogenous retroviruses leads to widespread transcriptional reprograming, affecting innate immune activation, metabolic control, and development. We find that the histone variant H2A.Z plays a central role in orchestrating these responses. Stimulating retroviral expression in zebrafish embryos causes H2A.Z to exit developmental gene promoters, which become silent, and to accumulate specifically at 'primed' repetitive elements, which are pre-marked by H3K27ac and H3K9me3. Remarkably, this rewiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Recent studies of zebrafish have found that sensitivity to environmental factors may also depend on the availability of source factors relative the sink capacity. In developing zebrafish embryos, exposure to either a common flame retardant, Tris(1,3-dichloro-2-propyl)phosphate, or a DNA methylation inhibitor, 5-aza-deoxycytidine, causes H2A.Z to accumulate specifically at transcriptionally active repetitive elements, including DNA transposons and satellite repeats ( Meng et al, 2022 preprint). These changes coincide with loss of H2A.Z at promoter regions, leading to transcriptional downregulation of genes proximal to impacted loci.…”
Section: Consequences Of Source-sink Disruptionmentioning
confidence: 99%
“…Recent studies of zebrafish have found that sensitivity to environmental factors may also depend on the availability of source factors relative the sink capacity. In developing zebrafish embryos, exposure to either a common flame retardant, Tris(1,3-dichloro-2-propyl)phosphate, or a DNA methylation inhibitor, 5-aza-deoxycytidine, causes H2A.Z to accumulate specifically at transcriptionally active repetitive elements, including DNA transposons and satellite repeats ( Meng et al, 2022 preprint). These changes coincide with loss of H2A.Z at promoter regions, leading to transcriptional downregulation of genes proximal to impacted loci.…”
Section: Consequences Of Source-sink Disruptionmentioning
confidence: 99%